Exploring the Impact of Constructivist Learning on Students' Prob-lem-Solving Abilities in Education - Renninger, Eryansyah Putra (Insan Akademika Publications, 2024)
This research explores the influence of the constructivist learning approach on students' problem-solving abilities within the context of education. Through a comprehensive review of existing literature, theoretical frameworks, and empirical studies, the study examines the complex interplay between pedagogical practices, cognitive processes, and learning outcomes. The research adopts a mixed-methods approach, synthesizing qualitative and quantitative data to provide a nuanced understanding of the efficacy of constructivist pedagogies in fostering critical thinking, creativity, and adaptive problem-solving skills among students. Significant correlations, differences, and trends observed in the data highlight the transformative potential of student-centered, inquiry-driven approaches in education. The implications of the findings for theory and practice in education are discussed, emphasizing the importance of aligning curriculum design, assessment practices, and professional development initiatives with constructivist principles. By bridging theory and practice, educators can cultivate problem-solving minds and empower students to thrive in an increasingly complex and interconnected world.